Quantifying nitrous oxide emissions from sugarcane cropping systems: Optimum sampling time and frequency. (July 2016) - Reeves, Steven; Wang, Weijin; Salter, Barry; Halpin, Neil
Abstract: Nitrous oxide (N2 O) emissions from soil are often measured using the manual static chamber method. Manual gas sampling is labour intensive, so a minimal sampling frequency that maintains the accuracy of measurements would be desirable. However, the high temporal (diurnal, daily and seasonal) variabilities of N2 O emissions can compromise the accuracy of measurements if not addressed adequately when formulating a sampling schedule. Assessments of sampling strategies to date have focussed on relatively low emission systems with high episodicity, where a small number of the highest emission peaks can be critically important in the measurement of whole season cumulative emissions. Using year-long, automated sub-daily N2 O measurements from three fertilised sugarcane fields, we undertook an evaluation of the optimum gas sampling strategies in high emission systems with relatively long emission episodes. The results indicated that sampling in the morning between 09:00–12:00, when soil temperature was generally close to the daily average, best approximated the daily mean N2 O emission within 4–7% of the 'actual' daily emissions measured by automated sampling. Weekly sampling with biweekly sampling for one week after >20 mm of rainfall was the recommended sampling regime. It resulted in no extreme (>20%) deviations from the 'actuals', had a high probability of estimating the annual cumulative emissions within 10% precision, with practicable sampling numbers in comparison to other sampling regimes. This provides robust and useful guidance for manual gas sampling in sugarcane cropping systems, although further adjustments by the operators in terms of expected measurement accuracy and resource availability are encouraged. By implementing these sampling strategies together, labour inputs and errors in measured cumulative N2 O emissions can be minimised. Further research is needed to quantify the spatial variability of N2 O emissions within sugarcane cropping and to develop techniques for effectively addressing both spatial and temporal variabilities simultaneously. Highlights: Year-long sub-daily N2 O emissions data from 3 sites used to assess sampling strategy. Sampling in daytime between 09:00 and 12:00 best estimated daily mean N2 O emissions. Weekly sampling + biweekly sampling for one week after >20 mm rainfall most efficient. Applying sampling recommendations will reduce errors in manual chamber measurements. Sampling schedules achieve greater accuracy in higher emission systems.